Correlation between inteligence and dimensions of personality and school succes - Matešić, Kruno ml (Array, 2008)
The correlation between intelligence and personality and academic success was examined on a sample of 3rd year high school students from various high schools. The NEO-FFI was used to measure fi ve personality dimensions (Neuroticism, Extroversion, Openness to Experience, Agreeableness and Conscientiousness) and the D-48 intelligence test with a highly saturated » g« factor. Academic success was defi ned by grades for mathematics and Croatian as well as the final, half-term overall grade. Intelligence showed a statistically signifi cant but relatively low correlation with the three most relevant indicators of academic success. A possible explanation is that nominally identical grades received by students from various classes are not obtained by students of equal intelligence. Conscientiousness was the strongest individual predictor of all three academic success criteria. The result is not surprising in view of the fact that conscientiousness is connected with work ethics, the need to succeed and personal organization. The structure of predictor variables for general success and Croatian language criteria is practically identical. Conscientiousness is followed by intelligence and introversion in the prediction of these criteria. Mathematics has a different relationship structure with intelligence measures and personality. The prediction ratio of intelligence has increased and is just below conscientiousness. A signifi cant predictor of mathemathical success is lower. Agreeableness, while Extroversion does not play a significant role. A possible explanation is persons with lower agreeableness scores are prone to critical thinking which contributes to accurate analyses in science and mathematics. The obtained fi ndings support data on personality measures playing a more significant role than intelligence in later educational phases, while intelligence is a stronger predictor of academic success in primary school.